Characteristics Of Herpes Zoster Patients At The Dermatology And Venereology Outpatient Clinic Of Wangaya Regional Hospital From January 2021 - December 2024 - Ida Ayu Trisna Wulandari; Putu Ayu Krisna Cahyaning Putri; Putu Eksa Bidja; Ida Ayu Uttari Priyadarshini (International Medical Journal Corp. Ltd, 2025)
Introduction: Herpes zoster (HZ) is a clinical condition resulting from the reactivation of the varicella zoster virus (VZV), typically presenting as painful, unilateral vesicular eruptions. Its incidence tends to increase with advancing age and in individuals with compromised immune systems. Objective: This study aims to describe the demographic and clinical characteristics of patients diagnosed with HZ at the Dermatology and Venereology outpatient clinic of Wangaya Regional Hospital. Methods: A retrospective, descriptive study was conducted using a cross-sectional design. Secondary data were obtained from medical records of patients diagnosed with HZ between January 2021 and December 2024. A total sampling method was applied, including 56 eligible patients. Results: The highest proportion of patients was in the 61–80-year age group (30.36%), followed by those aged 41–60 years (28.57%). Females accounted for 53.57% of cases. Vesicular and/or bullous lesions were the most common presentation (89.28%), with the thoracic dermatome being the most frequently affected region (44.64%). A majority of patients (60.71%) had no comorbidities; however, hypertension was the most prevalent comorbid condition (27.28%). Most patients (80.36%) received combination therapy comprising oral antivirals and topical agents. Post-herpetic neuralgia (21.43%) was the most commonly reported complication. Conclusion: Herpes zoster predominantly affects elderly individuals, particularly involving the thoracic dermatomes. Early diagnosis and appropriate management are crucial in minimizing complications.